Burden among caregivers of geriatric people in Kavrepalanchok district, Nepal - Manandhar, Nirmala; Shrestha, Sophiya; Risal, Ajay; Kunwar, Dipak; Manandhar, Kedar (Journal of Kathmandu Medical College, 2021)
Background: Ageing is the natural phenomenal encompassing physical, psychological, and social changes. Today, people are living longer than ever before due to advances in education, technology, medicine, food distribution, and public health. Longevity has also resulted in a care giving burden in the family living together.Objectives: To assess the caregiver’s burden among family of geriatric people in Kavrepalanchok.Methods: Analytical cross-sectional study was done to assess the caregivers’ burden among family members of geriatric people in Kavrepalanchok. Total sample of 439 was selected using multistage random sampling technique. Among them 21 respondents did not respond. Data were collected from January and February 2019 using validated Nepali version of the Zarit Burden Inventory-22. Descriptive and inferential statistic (t-test and ANOVA) were applied using Statistical Package for Social Sciences 20 version. The scoring ?21 on ZBI-22 were considered as burden.Results: The study showed that more than half respondents 256 (58.3%) had no or minimal burden, 183 (41.7%) experienced mild to severe burden while caring the older people at home. There was significant association between caregiver’s burden with age, education status, marital status, and occupation respectively.Conclusion: Care giving to elderly is stressful task which affects physical, mental, social, and psychological state of caregivers. Therefore, it would be helpful, if community health organisations could conduct the educational programme for caregivers caring the older family members at home.